Gus Born: Scientific Reflections of Later Years, Inspiring the Next Generation of Blood Researchers. (17th November 2018) - O'Donnell, Valerie B.
ABSTRACT: I am delighted to have been be asked by Steve Watson to write a short piece for this series in Platelets, on my friendship with Prof Gus Born which began in 2011, when he came to Cardiff to present at our UK Platelets meeting. Gus was an insipiration, his story resonates today and it is an honour to have the opportunity to record a summary of our meetings here.